Spatial distribution and determinants of limited access to improved drinking water service among households in Ethiopia based on the 2019 Ethiopian Mini Demographic and Health Survey: spatial and multilevel analyses - Alemayehu, Meron Asmamaw; Agimas, Muluken Chanie; Shewaye, Daniel Alayu; Derseh, Nebiyu Mekonnen; Aragaw, Fantu Mamo (Frontiers in Water, 2023)
Introduction Safe and easily accessible drinking water service generates substantial benefits for public health and the economy. Approximately 10% of the global burden of disease worldwide could be prevented with improved access to drinking water. The death of 30% of children younger than 5 years in developing countries is attributable to inadequate access to improved drinking water. Despite the presence of abundant water sources in Ethiopia, uneven distribution and waste pollution coupled with unprecedented population growth, rapid urbanization, and climate change are hindering the country's ability to maintain the balance between the demand and supply of accessible and improved drinking water services. The importance of up-to-date evidence for actions regarding the distribution of access to improved drinking water services is indicated by the Ethiopian Ministry of Water and Energy. Therefore, this study aimed to explore the spatial distribution and determinants of limited access to improved drinking water service among households in Ethiopia. Methods This study used the 2019 Ethiopian Mini Demographic and Health Survey (EMDHS). The data were weighted using sampling weight to restore the representativeness and to obtain valid statistical estimates. After excluding ineligible households, a total weighted sample of 5,760 households was included in the final analysis. The analysis was performed using STATA version 14.2, ArcGIS Pro, and SaTScan version 10.1 software. To find significant determinants with limited access to improved drinking water service, we used a multilevel logistic regression model. A P-value of <0.05 was used to declare statistical significance. Results This study found that in Ethiopia, 16.1% (95% CI: 15.2, 17.1) of households have limited access to improved drinking water services. The spatial distribution of households with limited access was identified to be clustered across a few regions of the country (Moran's I = 0.17, p-value < 0.01). The most likely significant primary clusters with highly limited access were seen in the Somali region (RR = 4.16, LLR = 162.8), the border between Amhara and Afar region (RR = 4.74, LLR = 41.6), the border between Oromia and Afar region (RR = 5.21, LLR = 13.23), and the northeastern Tigray region (RR = 2.52, LLR = 9.87). The wealth index, the age of household head, residence, and region were significantly associated with limited access to improved drinking water service. A high rate of limited access to improved drinking water service is predicted in the southwestern part of Gambella, the northeastern part of Oromia, the southwestern part of South Nation Nationalities and Peoples' region, and part of the Oromia region that surrounds Addis Ababa. Conclusion Limited access to improved drinking water service in Ethiopia varies across regions, and inequality in the service provision exists in the country. Prioritization and extra level of efforts should be made by concerned government and non-government organizations as well as other stakeholders for those underprivileged areas and groups of the population as they are found in the study.